EDUKASI TENTANG PEMBERIAN ASI EKSKLUSIF PADA WANITA HAMIL TRIMESTER III DI PUSKESMAS BASARANG KABUPATEN KAPUAS - Bella Bella; Nita Kusuma Lindarsih; Ivana Devitasari; Yulanda Esteriani (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Exclusive breastfeeding is a crucial measure for improving maternal and infant health; however, pregnant women's knowledge regarding the benefits and practices of breastfeeding still requires improvement. This community service activity aimed to enhance the knowledge of third-trimester pregnant women regarding exclusive breastfeeding at the Basarang Community Health Center (Puskesmas), Kapuas Regency. The method employed involved health education—delivered through interactive lectures, discussions, Q&A sessions, and the distribution of leaflets—to 15 third-trimester pregnant women. Evaluation was conducted using pre-tests and post-tests. The results showed an increase in the average knowledge score from 62.0 to 88.7 following the education. The proportion of participants with a